The Influence of Knowledge Management and Service Quality on E-Commerce Customer Satisfaction with Digital Literacy as a Moderator - Muhammad Junaid Kamaruddin Junet; Fauziah; Harisuddin (MJK PUBLISHER, 2026)
This study examines the effects of knowledge management and service quality on e-commerce customer satisfaction, with digital literacy serving as a moderating variable. Amid the rapid growth of the digital economy, customer satisfaction has become a key factor in sustaining the competitiveness of e-commerce platforms. A quantitative approach was employed using questionnaire data collected from e-commerce users and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The results indicate that knowledge management and service quality have positive and significant effects on customer satisfaction, while digital literacy strengthens these relationships. These findings highlight that effective knowledge management, high service quality, and digital literacy are critical factors in enhancing customer satisfaction and supporting the success of e-commerce businesses.